DESKRIPSI MOTIVASI WISATAWAN YANG BERKUNJUNG KE OBJEK WISATATABEK INDAH - Biyatmi Biyatmi; Sudarmi Sudarmi; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research was to examine about the tourists’ motivation describe in visiting Tabek Indah tourism object at Pemanggilan Village, Natar district, Southern Lampung year of 2011, with the point of studies on motivation of relaxation, sports, recreation, dating, visiting family/friends, hobbies, and working.This research used descriptive method. The population of the research were 60 wisatawants who were taken by quota sampling on the wisatawant. Data collection was carried out by observation techniques, structured interview of wisatawants, and documentation. The researcher used the tables and percentages data analysis as interpretation and description in giving explanation for the data in order to provide a report on this research.Tabek Indah tourism object has tourism potential which is the natural panorama, in the form of a beautiful natural landscape, cool air and equipped with the fishing pond, outbond ,and variety of rides. It becomes an attraction for tourists to visit Tabek Indah tourism object.The results of this research indicated that: (1) tourists’ motivation of relaxation were 51 wisatawants (85%), (2) tourists’ motivation of sports were 27 wisatawants (45%), (3) tourists’ motivation of leisure were 49% wisatawants (81,67%), tourists’ motivation for dating were 35 wisatawants (58,33%), (4) tourists’ motivation of visiting family/friends were 31 wisatawants (51,67%), (5) (6) tourists’ motivation of hobby were 23 wisatawants (38,33%), (7) tourists’ motivation of working were 3 wisatawants (5%).From the seven motivation the most dominant one is:1.      Tourists’ motivation of relaxation were 51 wisatawants (85%).2.      Tourists’ motivation of leisure were 49% wisatawants (81,67%).3.      Tourists’ motivation for dating were 35 wisatawants (58,33%).Keywords: Tourists’ motivation, relaxation, sports, recreation, dating, visiting family/friends, hobbies, and working.